The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1365-2826.2011.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence of Kisspeptin-Gonadotrophin-Releasing Hormone (GnRH) Interaction in the Median Eminence of Female Rats: Implication of Axo-Axonal Regulation of GnRH Release

Abstract: The present study was conducted to determine the morphological and functional interaction between kisspeptin and gonadotrophin-releasing hormone (GnRH) neuronal elements at the median eminence in female rats to clarify a possibility that kisspeptin directly stimulates GnRH release at the nerve end. A dual immunoelectron microscopic study of kisspeptin and GnRH showed that the kisspeptin-immunoreactive nerve element directly abutted the GnRH-immunoreactive nerve element, although no obvious synaptic structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 47 publications
3
84
0
2
Order By: Relevance
“…It has been demonstrated that the intracerebroventricular administration of KP induces luteinizing hormone (LH) secretion (Thompson et al 2004, Castellano et al 2005. Additionally, mRNA and immunohistochemistry analyses have demonstrated the presence of Kiss1R and KP in the stroma of GnRH neurons in the preoptic area and in axon terminals at the median eminence (Yamada et al 2007, Uenoyama et al 2011. Furthermore, the presence of KP and its actions have been demonstrated in many peripheral organs (Vikman & Ahren 2009, Pinilla et al 2012 such as the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the intracerebroventricular administration of KP induces luteinizing hormone (LH) secretion (Thompson et al 2004, Castellano et al 2005. Additionally, mRNA and immunohistochemistry analyses have demonstrated the presence of Kiss1R and KP in the stroma of GnRH neurons in the preoptic area and in axon terminals at the median eminence (Yamada et al 2007, Uenoyama et al 2011. Furthermore, the presence of KP and its actions have been demonstrated in many peripheral organs (Vikman & Ahren 2009, Pinilla et al 2012 such as the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the specificity of the antibodies, anti-Fos, -NKB and -kisspeptin antibodies were preabsorbed, respectively, with human Fos peptide (Oncogene Science, Cambridge, MA, USA), human NKB (Sigma-Aldrich, St. Louis, MO, USA), or sheep kisspeptin partial peptide, [Cys 37 ]sheep kisspeptin (37-53), which is a homologous peptide of [Cys 36 ]rat kisspeptin (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), the immunogen generating the antibody [25]. Both were subjected to immunohistochemistry as mentioned above.…”
Section: Immunohistochemical Controlsmentioning
confidence: 99%
“…Third, axons, including kisspeptin, produce an extensive and intimate association with GnRH axon terminals at the median eminence in goats [16,37] and monkeys [38]. Recent electron microscopic observations have revealed that kisspeptin axons are closely associated with GnRH axons in goats [37] and rats [39]. Fourth, GnRH neurons express Kiss1r [10] but not NK3R [12] in sheep.…”
mentioning
confidence: 99%
“…The studies performed on human autopsy samples recently have confirmed that kisspeptin neurons in humans are mainly located in the infundibular (arcuate in other species) and rostral preoptic area (POA) of the hypothalamus [24,29]. Studies have also indicated direct participation of kisspeptin in GnRH secretion [30], as evidenced by kisspeptin receptor mRNA expression by GnRH neurons [31,32], and close connections found between kisspeptin and GnRH neurons [22,24,26], although in humans not all GnRH neurons showed close connection with kisspeptin neurons [22,24,26,33].…”
Section: Functional Neuroanatomy Of the Kisspeptin Systemmentioning
confidence: 81%